Reconhecimento de territórios tradicionais: o contrato de concessão de direito real de uso enquanto instrumento de garantia do direito ao território tradicional - ARAÚJO, Marlon Aurélio Tapajós (Universidade Federal do Pará, 2017)
This dissertation is to study object recognition of traditional territories. Specifically, this was to assess the degree which granted autonomy to the region's traditional communities Juruti Velho, Juruti, Pará, through the Concession of Real Right to Use (CDRU) under Agroextrativista Project (LAP) led by Regional Superintendent of the Institute of Colonization and Agrarian Reform (INCRA) in Santarém. For this analysis was chosen as theoretical notions of legal pluralism, territoriality specific, agroecological possession, all point towards a right to traditional territory. Yet proceeded to a comparison between the model adopted for the regularization and the Extractive Reserves Project Agroextrativista since both draw on the CDRU for purposes and audiences alike, namely to ensure the right people to the territory and traditional communities. It concludes with an analysis of the specific situation of the traditional communities of Old Juruti from the norms to be established in the Management Plan as well as the mineral rights under the law of the territory. This analysis allowed to answer the question the research problem concerning the autonomy of traditional communities in the management of its territory.